Talking Local: Florida Consumers’ Flexibility with the Term “Local” - Lauri M. Baker; Caroline G. Roper; Meridith M. Oglesby; Olivia K. Doyle; Valentine Castano; Joy N. Rumble (EDIS)
This EDIS publication is the fifth of the Talking Local series, a six-part EDIS publication series about Florida consumers and their perceptions of local food. This series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally produced products. This series provides information about Florida consumers’ perceptions of local food to Extension faculty who are interested in local food programming or who work with local food clientele.